1993
DOI: 10.1007/bf02545304
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of the autoxidation of fats

Abstract: The mechanism of fat autoxidation is elucidated from the rate data. All the data treated here and in an earlier publication follow the same basic rate equation, including the time function fit} empirically derived for heterogeneous oxidation. Metals and glass (the wall of the reaction vessel} are catalysts. Depending on the state of the catalyst, fit) = t 2 or fit} = t. When fit} = t, the kinetics are first-order as found for monolayer autoxidation, but in bulk phase they are complicated by a transient stage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…The kinetics of autoxidation have usually been considered for the individual steps (Labuza, 1971;Brimberg, 1993;Simic et a/., 1992). …”
mentioning
confidence: 99%
“…The kinetics of autoxidation have usually been considered for the individual steps (Labuza, 1971;Brimberg, 1993;Simic et a/., 1992). …”
mentioning
confidence: 99%
“…Because this process usually includes initiation, propagation, and termination steps, its kinetics has also been studied for each step. 2,3) Ö zilgen and Ö zilgen 4) reported that the autocatalytic-type expression, a very simple equation, well describes the entire oxidation process of lipids. We also showed that the expression is applicable to the oxidation processes of fatty acids and their alkyl and glycerol esters.…”
mentioning
confidence: 99%
“…The kinetics of oxidation of different fatty acid substrates, treated in four preceding papers [5][6][7][8], seem to follow the same basic mechanism(s) emphasizing the importance of aspects related to heterogeneous oxidation [9][10][11]. Autoxidation is characterized by three kinetic stages with defined time ranges: the induction period, the autoxidation stage, and the last stage with constant rate of oxygen absorption [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%